2008
DOI: 10.1111/j.1464-410x.2008.07535.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management in selected patients with upper tract urothelial carcinoma compares favourably with early radical surgery

Abstract: OBJECTIVE To compare the outcomes of patients treated for upper tract urothelial carcinoma with either immediate nephroureterectomy (NU) or initial endoscopic management. PATIENTS AND METHODS The treatments of 108 patients (120 renal units) at the authors’ institution were retrospectively reviewed and divided into two groups, i.e. those who received immediate NU and those who had conservative initial therapy, which included renal units solely treated with endoscopy with or without delayed NU. Overall and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 19 publications
4
62
0
4
Order By: Relevance
“…Estas técnicas fueron primeramente descritas en pacientes seleccionados tales como monorrenos, con insuficiencia renal o con tumores bilaterales. Al demostrar resultados oncológicos comparables a la NUR 10 , aquellos pacientes con unidad renal contralateral normal y tumores de uréter distal, sobre todo de bajo grado de malignidad histológica, podrían ser candidatos a cirugía conservadora. Éstas pueden ir desde la resección endoscópica hasta la ureterectomía distal con neoimplante vesicoureteral mediante diferentes técnicas.…”
Section: Discussionunclassified
“…Estas técnicas fueron primeramente descritas en pacientes seleccionados tales como monorrenos, con insuficiencia renal o con tumores bilaterales. Al demostrar resultados oncológicos comparables a la NUR 10 , aquellos pacientes con unidad renal contralateral normal y tumores de uréter distal, sobre todo de bajo grado de malignidad histológica, podrían ser candidatos a cirugía conservadora. Éstas pueden ir desde la resección endoscópica hasta la ureterectomía distal con neoimplante vesicoureteral mediante diferentes técnicas.…”
Section: Discussionunclassified
“…Hence, we selected the one with more areas and patients. After rounds of screening, twenty-three studies including 1587 KS and 3996 NU patients were enrolled meta-analysis at last (Hall et al, 1998;Shiraishi et al, 2003;Chen et al, 2005;Roupret et al, 2006;Giannarini et al, 2007;Lehmann et al, 2007;Lucas et al, 2008;Dragicevic et al, 2009;Gadzinski et al, 2010;Jeldres et al, 2010;Raymundo et al, 2011;Bin et al, 2012;Bing-bing et al, 2012;Colin et al, 2012;Grasso et al, 2012;Bagrodia et al, 2013;Cutress et al, 2013;Fajkovic et al, 2013;Klatte et al, 2013;Dalpiaz et al, 2014;Fukushima et al, 2014;Hoffman et al, 2014;Hung et al, 2014). All included studies were retrospective comparative study; no randomized controlled trials were identified.…”
Section: Literature Filtration and Quality Assessmentmentioning
confidence: 99%
“…the 20q13.2 gain [5]. Moreover, the possible importance of many other molecules has been suggested and it is likely that in the next 5-10 years there could be a group of molecular and genetic markers [1]. They suggested conservative treatment followed by strict surveillance and delayed NU when progression will not compromise the oncological outcome, especially for patients with low-grade disease.…”
Section: Shiu-dong Chungmentioning
confidence: 99%